Systematic Literature Review: Upaya Meningkatkan Kemampuan Penalaran Matematis - Khoirunnisa, Mustika; Meiliasari (Jurnal PEKA (Pendidikan Matematika), 2025)
One of the key learning goals for mathematics in schools is the development of mathematical reasoning skills. The goal of this study is to review research on several initiatives to enhance mathematical reasoning skills conducted between 2019 and 2024. The Systematic Literature Review (SLR) technique is employed in this study, which chooses all articles—both domestic and foreign—that are indexed by at least Sinta 4 and Scopus in Google Scholar, Semantic, or via the journal URL. Several markers of mathematical reasoning ability were discovered based on the observations, and teachers can choose to employ methodologies, learning models, and instructional resources to help students become more proficient in mathematical reasoning. Approaches in the process that can be used include contextual approaches, metaphorical approaches, and RME. Learning models that can be chosen include Problem-based learning, reflective, ECIRR, and Novick's. Then, teachers can also choose to develop learning media such as videos or e-modules and PROLIBRA which uses the geogebra application.